AGRICULTURAL LAND USE CONFLICT BETWEEN LANDLORDS AND MIGRANT FARMERS IN GHANA: AN EXAMINATION OF ISSUES AFFECTING DAGARA MIGRANTS IN THE BRONG AHAFO REGION - Fabian Dome Yelsang (European Scientific Journal, ESJ, 2013)
Land tenure has been a major issue in Ghana. Land is an important asset that improves the livelihoods of poorer groups in every society, the world over. Farmer livelihood decisions as regards cropping strategies and input are strongly influenced by land tenure arrangements. Efforts by investors particularly migrants who need land to invest are hampered by the tenurial arrangements prevailing in our societies as is the case of Wenchi traditional area. Rights to land by these migrants are limited as the indigenous Bono are not willing to lease land for longer periods for long term investment purposes. They argue that migrant farmers from north-west of Ghana do not usually put the land to efficient use for it to maintain some level of nutrients. Another argument is that migrant farmers always try to cheat them on their own land by hiding some of the produce from their landlords. The migrants also argue that once they are not allowed to take greater percentage of farm produce from the farm, it would not be economical for them to manage the land the way their landlords want them to do. They argue further that cost of input on the farms is borne by them for only the landlords to get almost the same benefits as them (under the Abunu). Therefore, the use of land breeds tension between the two parties. A case study approach using Dagara migrant farmers from north western Ghana who migrate to Bono area in search of farm lands was used.An extensive literature review was also used in the methodology. The issues that emanated from the findings indicated that different communities and different people have their own ways of tenurial arrangements that result in conflicts most often. The conclusions drawn from the analysis show that conflict is pervasive due to disagreements over share of produce. It is recommended that efforts should be made by both parties to ensure that appropriate measures are put in place for efficient and appropriate land use by integrating customary and statutory policies.